Chitosan based architectures as biomedical carriers. (December 2022) - Sharma, Prem Prakash; Bhardwaj, Shakshi; Sethi, Aaftaab; Goel, Vijay K.; Grishina, Maria; Poonam,; Rathi, Brijesh
Abstract: In the recent past, chitosan demonstrated intriguing applications in the different domains of biomedical science, probably due to its biodegradability, biocompatibility, minimal toxicity, cost-effectiveness, and easy-going synthetic procedures. Chitosan is the second most prevalent amino polysaccharide after cellulose, generated from a deacetylated version of chitin. This short review briefly explains the preparation methods for chitosan from chitin and its role as a drug carrier for biomedical applications. Graphical abstract: Image 1 Highlights: Chitosan is a valuable biomaterial for biomedical science. It is biocompatible, minimal toxic, & cost-effective. Chitosan is the second most prevalent amino polysaccharide after cellulose. Applications of chitosan as a delivery vehicle are accomplished.